The role of the scribe according to the Mari texts: A study of terminology - Muntingh, L. M. (Journal for semitics, 1991)
After more than 50 years have passed since the discovery of the Old Babylonian city of Mari with its invaluable archive, new volumes of cunieform texts have recently been published. With all the material already available, we can study in depth the role of the scribe in the kingdom of Mari. In previous studies the ancient scribe was considered primarily as a secretary, though, as such, he became quite influential, especially when he was the secretary of a king. The numerous references in the Mari texts to scribes, by name, enable us to determine their role more specifically.